The Impact of Foreign Intervention in the Yemeni Crisis (2015-2020) - alhuniti, Rashed Ahmad Rashed (Dirasat: Human and Social Sciences, 2023)
Objectives: The research reviews the complications and effects of regional and international external interventions on the Yemeni crisis and determines its role in the crisis. Methods: For this purpose, the study relied on collecting data in a detailed manner through interviews with influential figures in the Yemeni issue, which helped to have a comprehensive understanding of the research questions and answer them in a scientific, objective, and accurate manner. Furthermore, the study outlined all factors influencing the conflict in Yemen, detailing their roles in shaping the situation. Results: The results indicated that the Saudi leadership showed greater resolve towards the Yemeni issue, while the Russian policy towards the Yemeni crisis was neutral. The UAE was the most active party in the Yemeni crisis, as it supported the loyal factions, and strongly supported the military formations it established. The study highlighted the danger of Iranian intervention in Yemen's internal affairs and its impact on the stability and security of the region's countries. The study highlighted the Saudi leadership's more decisive role in addressing the Yemeni issue compared to other critical foreign policy matters like those in Syria and Iraq. Conclusions: The study found that the objectives of Saudi Arabia's military intervention in its southern neighbor, Yemen, remain unclear. Despite initially announced goals of altering the emergency, supporting President Hadi, and consolidating control, there seems to be a shift toward fostering a loosely unified state that accommodates various factions, including temporary support for separatists in the south without complete appeasement.